Keanekaragaman Jenis Burung di Wana Wisata Kawah Putih dan Sekitarnya Kabupaten Bandung Provinsi Jawa Barat - Eltriadi, Piero Nandata; Jihad, Nidaul; Elllysa, Siti; Dhava, Rafif Aulia; Kurnia, Insan; Prasetyo, Budi; Komarudin, Komarudin (Jurnal Penelitian Sains, 2024)
Kawah Putih is managed by Perum Perhutani Unit III Jawa Barat dan Banten with protected forest status as well as a tourist area in the form of the Kawah Putih Tourism Area (WWNP). The main attraction is the white crater as a mountain caldera from the eruption of Mount Patuha at an altitude of 2400 meters above sea level. This area is a mountainous tropical rainforest remaining on the island of Java so it is special in relation to biodiversity data including birds. Therefore, this study aims to analyze bird diversity in WWNP and its surroundings. The research was carried out in July 2022 using the MacKinnon list and index point abundance. Data was analyzed qualitatively, namely the status of bird species and quantitatively by calculating species diversity index (H') and species evenness (E). The richness of bird was found to be 67 species from 29 families and seven orders. There are 10 species of birds protected by the Indonesian Government and two types are included in IUCN threathened species. All species are resident, there are no migrant species. Eight species are endemic to Java and three species are endemic to Java-Bali. Some species are typical mountain birds. Comparison with previous research shows that 25 species were recorded again, 24 were not recorded again, and 42 species were new records. The H' value obtained is included in the high diversity category, namely 3.73, as well as the E value, which is in the high evenness category, namely 0.89.